Biostimulant effects of poultry feather hydrolysate on wheat and soil: effects of addition rate and state - Roy, Aditi; Jílková, Veronika (Frontiers in Agronomy, 2025)
The growing need for sustainable agricultural practices has intensified interest in alternative soil amendments such as poultry feather hydrolysate (PFH), a nutrient-rich biostimulant derived from poultry industry waste. Despite the promising benefits of PFH in promoting plant growth and improving soil health, its effectiveness in soil application across different addition rates and states remains underexplored. This study assessed the effects of PFH applied on the soil surface at no, low (4 t dw ha–1) and high (8 t dw ha–1) addition rates in either liquid or solid states on wheat (Triticum aestivum L.) biomass growth and soil properties in a 3-month controlled pot experiment. Irrespective of the addition rate, PFH consistently increased wheat shoot and root biomass by up to 109% and 74%, respectively, with stronger cumulative effects observed over time. The high addition rate significantly increased the soil organic matter (OM) content by 20% and improved the water-holding capacity by 9%, while concurrently reducing the pH by up to 7%. In the liquid state, PFH stimulated rapid biomass growth, microbial activity and dissolved nitrogen (DN) content, whereas in the solid state it sustained microbial activity and DN content over the longer term. Despite these changes, microbial biomass and OM stabilization remained unaffected. Overall, the results demonstrate that PFH, particularly in the liquid state, acts as a readily available nutrient source that promotes wheat growth and improves soil quality, offering a practical and sustainable option for organic waste recycling and nutrient management in cereal cropping systems.